miR-28: A Tiny Player in Cancer Progression and Other Human Diseases - Karol Kotarski; Marta Kot; Klaudia Skrzypek (Biomolecules, 2025)
MicroRNAs belong to a class of small non-coding RNA molecules that regulate gene expression post-transcriptionally. By binding to specific mRNA sequences, microRNAs can either inhibit translation or promote transcript degradation. MicroRNA-28 (miR-28) plays a pivotal role in regulating the processes responsible for the pathogenesis of numerous diseases. Its function is contingent upon the specific type of disease and the cellular microenvironment. miR-28 can act as both an inhibitor and inducer of pathogenic processes. This article discusses the impact of miR-28 on the progression of various types of cancer, with particular emphasis on its role as a regulator of gene expression involved in cell proliferation, apoptosis, invasion, migration, and metastasis. Additionally, the article delves into the role of miR-28 in other human diseases and its influence on the processes that underlie their development. A comprehensive understanding of the precise mechanisms through which this specific microRNA exerts its regulatory functions could significantly impact the development of novel therapies. Furthermore, there is potential for miR-28 to be utilized as a diagnostic and preventative biomarker.